Analisis Level Kognitif Soal-Soal Pemecahan Masalah Pada Buku Siswa Matematika Kelas VIII Kurikulum 2013 - HIDAYAT, RAHMAD; , Idris Harta, M. A. Ph. D (2016)
This reseach aims to describe the level of cognitive problems solving in math books at eighth grade curriculum of 2013. The research is a qualitative research. The research data is the problem in terms of mathematical cognitive level such knowledge and understanding, application and reason. The surces of data in this study are the questions in the math textbook ofeighthgradecurriculumof2013. Data collection techniques in this study using observation with the stage of determining teaching textbooks, teaching materials determination in accordance with the basic competence, determination of the problems in terms of cognitive level, and data usage. Data analysis technique is done by analyzing the cognitive level maths in the book by developing a table to define each cognitive level according to the lattice SMP 2016, then modified in diagram form as bar charts and pie charts. Furthermore, from the diagram will be described in narrative text. It can be concluded 1) level of cognitive knowledge and understanding of the math book in terms of cognitive level based on the lattice UN SMP 2016, there are 74 items with a percentage of 45,7%, 2) cognitive level applications on a book of mathematics in terms of cognitive level based on the lattice SMP 2016 there were 52 items with a percentage of 32,1%, 3) level of cognitive reasoning in mathematics books in terms of the cognitive level based on the lattice UN SMP 2016 there were 36 items with a percentage of 22,27%.